2021
DOI: 10.12681/jhvms.26744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-carnitine supplementation in diets of broiler chickens

Abstract: L-carnitine is a nutritional supplement having fat-burning property and plays an important role in lipid metabolism, energy release, and also improve the production yield, immunity and blood constitute. This paper reviews the effects of L-carnitine on quantitative and qualitative characteristics of broilers. According to the reviewed literature, the application of L-carnitine (50-200 mg/kg) has no significant effect on the growth performance, however, using L-carnitine as much as 300-800 mg/kg resulted to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Safari et al [16] found that the use of L-carnitine in narrow clawed crayfsh, Astacus leptodactylus, diets can infuence increase the production of haemolymph as well as enhance antioxidant enzymes. Te successful use of L-carnitine as a feed additive to improve antioxidant response has also been confrmed in broiler chickens [72], black carp (Mylopharyngodon piceus) [73], juvenile black sea bream (Sparus macrocephalus) [74] and rainbow trout (Oncorhynchus mykiss) [75]. In this study, the dog conch fed the diets supplemented with L-carnitine showed enhanced status of antioxidants and immunological enzyme activity.…”
Section: Discussionmentioning
confidence: 73%
“…Safari et al [16] found that the use of L-carnitine in narrow clawed crayfsh, Astacus leptodactylus, diets can infuence increase the production of haemolymph as well as enhance antioxidant enzymes. Te successful use of L-carnitine as a feed additive to improve antioxidant response has also been confrmed in broiler chickens [72], black carp (Mylopharyngodon piceus) [73], juvenile black sea bream (Sparus macrocephalus) [74] and rainbow trout (Oncorhynchus mykiss) [75]. In this study, the dog conch fed the diets supplemented with L-carnitine showed enhanced status of antioxidants and immunological enzyme activity.…”
Section: Discussionmentioning
confidence: 73%
“…За споживання БВМД з карнітином підвищились показники перетравності сирої клітковини та сирого жиру раціону на 11,9 та 6,17 % відповідно . L-карнітин -вітаміноподібна речовина, регулює білковий та жировий обмін, стимулює секреторну активність залоз травного тракту, сприяє підвищенню ферментативної активності шлункового і кишкового соку (Azizi-Chekosari et al, 2021).…”
Section: вступunclassified
“…The inclusion of L-carnitine in the diet has been associated with improvements in energy efficiency, body weight gains, and feed conversion ratio in poultry. Additionally, L-carnitine has been observed to enhance the antioxidant and immune capacity of poultry ( Azizi-chekosari et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%